Analisa Pengaruh Excess Air Terhadap Efisiensi Pembakaran Boiler Jenis Pulverizer Coal 230 T/H - Muholad, Wildan; Hasbi, Muhammad; Endriatno, Nanang (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2021)
To save on coal consumption in PLTU (Steam Power Plant), it is necessary to increase boiler efficiency. The factors that can affect boiler efficiency include: flue gas temperature, fuel specification, excess air, ambient temperature, radiation and convection losses. By changing the value of excess air in this case the percentage of oxygen (4% to 4.5%) will affect the efficiency of the boiler. Changing the value of excess air also results in a change in the electrical power used by the auxiliary system in the boiler. Calculation of boiler efficiency with the direct method by testing 2 times on each oxygen percentage value of 4% and 4.5. Efficiency increased 0.94%, from 80.76% to 81.7% in test 1 and increased 1.02%, from 90.81% to 91.83% in test II. The power usage increased by 27.959 Kw in the 1st test and increased to 26.663 Kw in the test II.Kata kunci: Boiler, efficiency, excess air, PLTU